Pengaruh Motivasi, Kompetensi, Kepemimpinan, Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Guru di Sekolah Menengah Kejuruan - Anam, Chairul (Universitas Pesantren Tinggi Darul 'Ulum, 2018)
This study aims to determine the effect of motivation, competence, leadership, work environment and work discipline on teacher performance. After testing, it is concluded that motivation, competence, leadership, work environment have a significant effect on teacher performance. While the work discipline has no significant effect on teacher performance. It is simultaneously known that there is a significant influence between motivation, competence, leadership, work environment and work discipline collectively on teacher performance. Based on statistical test, adjusted R square (R2) is 0,736 or 73,6% indicating that 73,6% change of teacher performance variable can be explained by motivation, competence, leadership, work environment and work discipline, while the rest 26,4% explained by other variables outside the model. The result of 0.736 shows the correlation between the independent variables simultaneously to the employee performance variable has a strong correlation. While in each independent variable affect the performance of teachers are as follows: Y = 1.616 + 0.463 X1 + 0.352 X2 + 0.373 X3 + 0.635 X4 + 0.250 X5, meaning constants. Based on T test, it is found that for competence and performance variables have no effect on teacher performance, and other variables have an effect. For F test obtained the result that together independent variable influence on teacher performance at SMK NU Mojoagung Superior Jombang.